2008
DOI: 10.3844/ajassp.2008.355.368
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation Into the Behavior of Circular Pad Shallow Foundations Supported by Geogrid Reinforced Sand

Abstract: This study seeks to widen the pool of knowledge on the use and characteristics of geosynthetics, specifically in the area of circular foundations supported by geosynthetic reinforced sand. The main objective of the work was to increase the awareness of circular foundation systems and thus increase the accuracy of current laboratory methods. Also, compare the results with that of previous papers on the subject and to provide new model curves to estimate the bearing capacity of circular foundations. In this resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…Also the results obtained show that the pressure-settlement curves for N=3 and N=4 are very close to each other. This contribution coincides with researches performed by Akinmusuru and Akinbolade (1981), Guido et al (1985), Marandi et al (2008) reported that the increase in bearing capacity for single reinforced footing is not much tangible when the number of reinforcement layers is greater than 3 [4,11,23]. However, Das and Omar (1994) and Boushehrian and Hataf (2003) reported that for a single reinforced footing the optimized N is 4 [7,9].…”
Section: The Number Of Geogrid Layers (N)supporting
confidence: 87%
See 1 more Smart Citation
“…Also the results obtained show that the pressure-settlement curves for N=3 and N=4 are very close to each other. This contribution coincides with researches performed by Akinmusuru and Akinbolade (1981), Guido et al (1985), Marandi et al (2008) reported that the increase in bearing capacity for single reinforced footing is not much tangible when the number of reinforcement layers is greater than 3 [4,11,23]. However, Das and Omar (1994) and Boushehrian and Hataf (2003) reported that for a single reinforced footing the optimized N is 4 [7,9].…”
Section: The Number Of Geogrid Layers (N)supporting
confidence: 87%
“…The results of this research showed the effects of reinforcement layers on the bearing capacity changes and tilt over closely spaced footings. Marandi et al (2008) studied the behavior of circular foundation supported by geogridreinforced soil using finite element method [11]. The results of their research showed that the number of reinforcement layers greater than 3 does not considerably increase the bearing capacity.…”
Section: Introductionmentioning
confidence: 99%